2017
DOI: 10.1016/j.nicl.2017.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects and after-effects of acoustic coordinated reset neuromodulation in patients with chronic subjective tinnitus

Abstract: Chronic subjective tinnitus is an auditory phantom phenomenon characterized by abnormal neuronal synchrony in the central auditory system. As shown computationally, acoustic coordinated reset (CR) neuromodulation causes a long-lasting desynchronization of pathological synchrony by downregulating abnormal synaptic connectivity. In a previous proof of concept study acoustic CR neuromodulation, employing stimulation tone patterns tailored to the dominant tinnitus frequency, was compared to noisy CR-like stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 76 publications
3
42
0
1
Order By: Relevance
“…We here demonstrated that over a wide range of stimulation parameters favorable acute effects do not automatically lead to favorable long-lasting, sustained after-effects. This is in agreement with a computational study in the same model, but performed in only a restricted parameter range [78], as well as with an EEG experiment performed in tinnitus patients [114]. To characterize stimulation induced effects, we here used the average synaptic weight [Eq (10)] and the average amount of neuronal synchrony [Eq (11)].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We here demonstrated that over a wide range of stimulation parameters favorable acute effects do not automatically lead to favorable long-lasting, sustained after-effects. This is in agreement with a computational study in the same model, but performed in only a restricted parameter range [78], as well as with an EEG experiment performed in tinnitus patients [114]. To characterize stimulation induced effects, we here used the average synaptic weight [Eq (10)] and the average amount of neuronal synchrony [Eq (11)].…”
Section: Discussionsupporting
confidence: 69%
“…On the one hand this finding might inspire future computational and pre-clinical studies aiming at specifically designing stimulation protocols for long-lasting (as opposed to acute) desynchronization. On the other hand, this finding is significant for the development of clinical calibration procedures for CR stimulation, see [114].…”
Section: Discussionmentioning
confidence: 99%
“…Epidural recordings from the secondary auditory cortex in tinnitus patients showed that abnormal θ-band activity was highly correlated with tinnitus loudness. 97 Adamchic proposed that the temporal pattern of neurons plays a key role in shaping synaptic connections, 98 and this suggests that MEG might objectively reflect tinnitus by recording abnormal cortex activities.…”
Section: Discussionmentioning
confidence: 99%
“…Patients using CR showed a stable effect in on- and off-stimulation, while patients receiving noisy CR-like stimulation (the noisy CR-like stimulation shares the basic rhythmic CR pattern with CR, but the stimulation tones are randomly selected from a larger frequency range that are not related to the tinnitus pitch) only showed efficacy in on-stimulation. 26 , 68 Tass argued that ideally, the CR stimulation should be limited to the area of enhanced synchronized activity. The distance of the stimulation sites (frequencies) needs to be controlled, and the distance should be sufficient to achieve optimal desynchronizing CR effects.…”
Section: Acoustic Coordinated Reset Neuromodulationmentioning
confidence: 99%
“…As such, much work has been dedicated to identifying neural correlates of conscious tinnitus perception through comparison of spontaneous resting‐state oscillations in brain activity in individuals with and without tinnitus using silently acquired recording modalities that are noninvasive such as magnetoencephalography (MEG) or electroencephalography. In response to theories of aberrant oscillatory behavior in tinnitus and their supporting evidence, many proposed treatments are aimed at directly or indirectly altering oscillatory activity in the hopes of delivering symptom relief (Adamchic et al, 2017; Adamchic, Hauptmann, & Tass, 2012; De Ridder, Joos, & Vanneste, 2016; De Ridder, Song, & Vanneste, 2013; De Ridder & Vanneste, 2012; Hartmann, Lorenz, Müller, Langguth, & Weisz, 2014; Larson & Cheung, 2012, 2013; Silchenko, Adamchic, Hauptmann, & Tass, 2013; Weisz, Lüchinger, Thut, & Müller, 2014). Previous MEG studies investigating the functional pathology of tinnitus have resulted in mixed findings, with some studies suggesting functional abnormalities in and around auditory cortex (Hartmann et al, 2014) or in connectivity between auditory cortex and other brain regions (Zobay, Palmer, Hall, Sereda, & Adjamian, 2015).…”
Section: Introductionmentioning
confidence: 99%